2009
DOI: 10.1051/fruits/2008045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maturity stage of mango at harvest on its ripening quality

Abstract: Influence of maturity stage of mango at harvest on its ripening quality. Abstract-Introduction. The subjectivity of the external criteria used for the determination of mango maturity at its harvest led to the search for additional more reliable parameters to determine the optimal harvest maturity and able to replace the external and internal morphological indices. Materials and methods. Some physicochemical characteristics, such as colour of pulp, soluble dry extract, titratable acidity and weight loss, were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 5 publications
3
14
0
Order By: Relevance
“…Fruit firmness in plums decreased progressively with the increase in storage period at both the stages of maturity, primarily because there might have been progressive increase in fruit softening due to increased activities of PG and PME enzymes, rendering them much softer with the progressive increase in storage period. In general, fruit firmness decreases sharply with ripening, which is influenced by the stage at which fruits are harvested [2].…”
Section: Effects Of Ethylene Absorbents On Fruit Firmnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit firmness in plums decreased progressively with the increase in storage period at both the stages of maturity, primarily because there might have been progressive increase in fruit softening due to increased activities of PG and PME enzymes, rendering them much softer with the progressive increase in storage period. In general, fruit firmness decreases sharply with ripening, which is influenced by the stage at which fruits are harvested [2].…”
Section: Effects Of Ethylene Absorbents On Fruit Firmnessmentioning
confidence: 99%
“…Plums harvested at the climacteric stage usually attain an attractive peel colour and have better flavour than those harvested at the pre-climacteric stage. Thus, the stage of maturity at which fruits are harvested may also have a significant influence on colour, texture, fruit softening, enzyme activity and postharvest quality attributes [2]. Further, the perishable nature of ripe plum fruit poses a serious problem for its storage, transport and marketing.…”
Section: Introductionmentioning
confidence: 99%
“…Nakasone and Paul [9] reported that environmental factors such as light, wind, edaphic soil characteristics, temperature, soil relative humidity, and biotic factors such as mycorrhizal fungi and genotype significantly affect the productivity and physiology of papaya [11]. Besides environmental factors, fruit chemical features are also affected by location and season [5,12,13], and maturity stage [14]. Temperatures below 20°C have a very negative effect, causing among other problems, carpelloidy, sex changes, reduced pollen viability, and low sugar content of the fruit.…”
Section: Introductionmentioning
confidence: 99%
“…The recorded values for TSS in our experiment agree with those found by Dick et al for cv. Kent, which varied from (14.2 to 20)°Brix [50]. In addition, during 2008, the skin weight percentage was slightly higher in the fruits of trees of the SDI-1 and SDI-2 treatments than in those of the SDI-3 treatment and control.…”
Section: Vh Durán Zuazo Et Almentioning
confidence: 91%
“…The soil-water content (θv) during the irrigation season was recorded using the Frequency Domain Reflectometry (FDR) system (Diviner-Sentek Pty Ltd.), at (10,20,30,40,50, 60 and 70) cm soil depth.…”
Section: Methodsmentioning
confidence: 99%